2003
DOI: 10.1136/bjo.87.11.1350
|View full text |Cite
|
Sign up to set email alerts
|

Is visual outcome compromised when next day review is omitted after phacoemulsification surgery? A randomised control trial

Abstract: Aims: To examine the safety implications of omitting first day clinical review following phacoemulsification cataract surgery. Methods: 362 patients were randomly assigned to ''same day discharge'' (SDD) or ''next day review'' (NDR). All patients were reviewed approximately 2 weeks after surgery. Results: Of the 174 patients randomised to NDR, 14 (8.0%) were treated for raised intraocular pressure (25-48 mm Hg) on the first postoperative day. Four received increased topical steroids for uveitis (two) and corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 18 publications
3
39
0
3
Order By: Relevance
“…18,19 In addition, in our study, 89.5% of eyes achieved a postoperative visual acuity of 20/40 or better, which compares favorably with results in other studies of phacoemulsification in eyes with uveitis in which systemic corticosteroid therapy was used (73% with 20/30 or better 18 and 72% with 6/9 or better at last follow-up 19 ). This finding even compares well with results in some studies of eyes without uveitis, 20,21 in which approximately 80% of patients achieved a postoperative visual acuity of 20/40 or better.…”
Section: Visual Acuitysupporting
confidence: 83%
“…18,19 In addition, in our study, 89.5% of eyes achieved a postoperative visual acuity of 20/40 or better, which compares favorably with results in other studies of phacoemulsification in eyes with uveitis in which systemic corticosteroid therapy was used (73% with 20/30 or better 18 and 72% with 6/9 or better at last follow-up 19 ). This finding even compares well with results in some studies of eyes without uveitis, 20,21 in which approximately 80% of patients achieved a postoperative visual acuity of 20/40 or better.…”
Section: Visual Acuitysupporting
confidence: 83%
“…The VCM1 has been used in several studies [23][24][25], but underwent only minor revision following the CFA. The one item was deleted because it was conceptually different from the other items.…”
Section: Factor Analysismentioning
confidence: 99%
“…1,[4][5][6][7] However, in patients with glaucoma or OHT, this approach was not advocated. 1,4 The AAO recommends a review within 24 h for all patients at risk of an IOP spike.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] It has been suggested that the 1-day postoperative intraocular pressure (IOP) check post routine uncomplicated phacoemulsification can be abandoned for a number of reasons. 1,[4][5][6][7] Some of these include the fact that new surgical complications are unlikely to be picked up on the first day, peak IOP may have already passed, economical constraints, improved postoperative outcomes and low complication rates. 1,4 However in patients with glaucoma or ocular hypertension (OHT), either this approach was not advocated, or it was recommended that prophylactic regimes against a raised IOP should be followed as investigated in other studies.…”
Section: Introductionmentioning
confidence: 99%